2020
DOI: 10.1016/j.sjbs.2020.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of compound growth regulators on the anatomy of Jujube Leaf and Fruit

Abstract: Effects of three compound growth regulators formulated with hypersensitivity protein, spermidine, salicylic acid and DA-6 (diethyl aminoethanol hexanoate) were tested on Xinjiang Jun Jujube. The doses of compound growth regulators were named as A (Hypersensitivity protein + spermidine + salicylic acid at the rate of 30 mg/L, 0.1 mmol/L and 0.25 mmol/L, respectively), B (Hypersensitive protein + spermidine + DA-6 at the rate of 30 mg/L, 0.1 mmol/L and 30 mg/L, respectively) and C (Spermidine + salicylic acid + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The anatomical analysis in this study observed that the thickness of palisade tissue and spongy mesophyll signi cantly increased or did not change signi cantly under salt treatments (especially ≤ 30‰), which could lead to these photosynthesis and uorescence variation under salt stress. Because that thick palisade tissue could improve the photosynthetic e ciency of leaves 35 , large veins and parenchyma cells could help leaves to improve water transport e ciency and water storage capacity, respectively 36,37 . Furthermore, in previous study, the anatomical structure of roots and stems of plants are related to the salt tolerance 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical analysis in this study observed that the thickness of palisade tissue and spongy mesophyll signi cantly increased or did not change signi cantly under salt treatments (especially ≤ 30‰), which could lead to these photosynthesis and uorescence variation under salt stress. Because that thick palisade tissue could improve the photosynthetic e ciency of leaves 35 , large veins and parenchyma cells could help leaves to improve water transport e ciency and water storage capacity, respectively 36,37 . Furthermore, in previous study, the anatomical structure of roots and stems of plants are related to the salt tolerance 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical analysis in this study observed that the thickness of palisade tissue and spongy mesophyll signi cantly increased or did not change signi cantly under salt treatments (especially ≤ 30‰), which could lead to these photosynthesis and uorescence variation under salt stress. Because that thick palisade tissue could improve the photosynthetic e ciency of leaves 35 , large veins and parenchyma cells could help leaves to improve water transport e ciency and water storage capacity, respectively 36,37 . Furthermore, in previous study, the anatomical structure of roots and stems of plants are related to the salt tolerance 38 .…”
Section: Discussionmentioning
confidence: 99%
“…It is generally held that SA plays vital roles in plant stress tolerance. SA's main roles in plant tolerance to stresses can be summarized as following: the activation of plant defense mechanisms [2,[11][12][13][14], the improvement of photosynthesis [15][16][17][18][19][20][21][22], the regulation of plant normal growth and development [8,19,[23][24][25][26][27][28][29][30], and the enhancement of plant tolerance to drought [9,11,[31][32][33][34][35][36], cold [37][38][39], heat [36,[39][40][41][42], salt [43][44][45][46][47][48], and heavy metal stresses [49][50][51]…”
Section: Introductionmentioning
confidence: 99%
“…It was also generally considered that SA can be involved in the regulation of normal growth and development of plants [8,19,[23][24][25][26][27][28][29][30]. For example, SA can promote the differentiation of blossom buds, thus directly enhancing flowering [70,71].…”
Section: Introductionmentioning
confidence: 99%